THE DIGESTIBILITY VALUE OF COMMERCIAL RATIONS AND CONVENTIONAL RATIONS IN LAYING HENS ISA BROWN - N. N. A., Trisnayanthi; Astawa, I P. A.; Mahardika, I G. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the digestibility value of commercial and conventional rations in laying hens isa brown.This research was carried out in two places, the first in Candikusuma Village, Melaya District, Jembrana Regency, Bali and the second in the Nutrition and Animal Feed Laboratory, Faculty of Animal Husbandry, Udayana University which lasted for one months one week. The design used was a Completely Randomized Design (CRD) with 4 treatments and 4 replications, so there were 16 experimental units. Each experimental unit used 10 laying hens. The four treatments were laying hens that were given commercial feed (P0), laying hens that were given conventional rations 1(P1), laying hens that were given conventional rations 2 (P2), laying hens that were given conventional rations 3 (P3). Based on the results of this study, it can be concluded that commercial rations can increase the digestibility of dry matter and organic matter, and reduce digestibility of crude fiber and give the same results on digestibility of crude protein as conventional rations. Keywords : Laying hens Isa Brown, digestibility, commersial and conventional rations.